2015
DOI: 10.1371/journal.pone.0142011
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-Led Medication Reviews to Identify and Collaboratively Resolve Drug-Related Problems in Psychiatry – A Controlled, Clinical Trial

Abstract: Aim of the studyThis prospective, controlled trial aimed to assess the effect of pharmacist-led medication reviews on the medication safety of psychiatric inpatients by the resolution of Drug-Related Problems (DRP). Both the therapy appropriateness measured with the Medication Appropriateness Index (MAI) and the number of unsolved DRP per patient were chosen as primary outcome measures.MethodsDepending on their time of admission, 269 psychiatric patients that were admitted to a psychiatric university hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 42 publications
(50 reference statements)
4
37
7
Order By: Relevance
“…Though identifying, solving and preventing medication problems, finding out prescription errors and medication-related injuries by clinical pharmacists, incidence of adverse events and rehospitalization rates could be reduced. Patient adherence of the treatment could be significantly improved and possible harm due to medication problems had been reduced after patients received their medication instructions 2 . Medication education and treatment advice from clinical pharmacists could also shorten hospital stay 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Though identifying, solving and preventing medication problems, finding out prescription errors and medication-related injuries by clinical pharmacists, incidence of adverse events and rehospitalization rates could be reduced. Patient adherence of the treatment could be significantly improved and possible harm due to medication problems had been reduced after patients received their medication instructions 2 . Medication education and treatment advice from clinical pharmacists could also shorten hospital stay 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The intervention measures were adapted to the requirements of doctors in private practice after optimized communication with the hospitals. We did not aim to study the effect of individual modules or to evaluate the benefit of medication checks; other studies have already done so (1,2). Studies that were conducted in non-German speaking countries have shown that multifactorial problems at interfaces can be solved quickly by combining several measures in medication management (3).…”
Section: In Replymentioning
confidence: 99%
“…The intervention measures were adapted to the requirements of doctors in private practice after optimized communication with the hospitals. We did not aim to study the effect of individual modules or to evaluate the benefit of medication checks; other studies have already done so (1,2). Studies that were conducted in non-German speaking countries have shown that multifactorial problems at interfaces can be solved quickly by combining several measures in medication management (3).…”
Section: In Replymentioning
confidence: 99%